2019
DOI: 10.1088/1755-1315/355/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis and modelling of respiration rate of tropical climacteric produces during storage under various temperatures

Abstract: Many tropical agricultural products belong to climacteric group which need more attention to be able to extend or maintain their shelf life during storage. One of the most important phenomenon of climacteric produce is about the respiration rate of that produce. The following research was intended to investigate the rate of respiration of tropical climacteric products under various treatments including low temperature and the type of products. This research had developed respirometer device made from glass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…reported a higher respiration rate in small‐fruited ‘Hass’ avocado fruit. Similar results were also found in guava fruit, 46 unlike Rahayu and Bintoro 42 . Small‐fruited tomatoes in the ‘Unicorn’ cultivar of the cherry type had greater respiration at harvest time compared to large‐fruited tomatoes 47 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…reported a higher respiration rate in small‐fruited ‘Hass’ avocado fruit. Similar results were also found in guava fruit, 46 unlike Rahayu and Bintoro 42 . Small‐fruited tomatoes in the ‘Unicorn’ cultivar of the cherry type had greater respiration at harvest time compared to large‐fruited tomatoes 47 .…”
Section: Discussionsupporting
confidence: 74%
“…In mandarin, CO 2 production correlated negatively with rind thickness, and fruit size did not affect respiration rate 41 . Also, a study conducted with banana, guava and mango revealed that the size of the fruits was not related to the respiration rate 42 . However, in ‘Gala’ apple cultivar, as the fruits size, the respiration rate increases 43 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Fasilitas-fasilitas untuk melaksanakan penelitian pada bidang penanganan pascapanen produk segar di Indonesia masih sangat terbatas. Kebutuhan akan fasilitas yang memadahi merupakan hal yang penting untuk dapat mengembangkan teknologi pascapanen produk segar yang berkualitas (Rahayu dan Bintoro, 2019). Tujuan dari penelitian ini adalah untuk merancang dan membuat peralatan yang dapat mengatur suhu dan memodifikasi komposisi gas dari udara yang ada di dalam suatu ruangan tertutup yang secara umum dikenal sebagai Modified Atmosphere Storage (MAS).…”
Section: Pendahuluanunclassified